Mental Illness Stigma and Associated Factors among Arabic-Speaking Religious and Community Leaders - Klimentina Krstanoska-Blazeska (International Journal of Environmental Research and Public Health, 2021)
Evidence suggests that Arabic-speaking refugees in Australia seek help from informal sources, including religious and community leaders, when experiencing mental health issues. Despite their significant influence, there is scarce research exploring attitudes of Arabic-speaking leaders toward mental illness. The current exploratory study explored mental illness stigma and various factors among Arabic-speaking religious and community leaders. This study uses a subset of data from an evaluation trial of mental health literacy training for Arabic-speaking religious and community leaders. Our dataset contains the pre-intervention survey responses for 52 Arabic-speaking leaders (69.2% female; mean age = 47.1, SD = 15.3) on the ability to recognise a mental disorder, beliefs about causes for developing mental illness, and two stigma measures, personal stigma, and social distance. Being female was associated with a decrease in personal stigma. An increase in age was associated with an increase in personal stigma. Correct recognition of a mental disorder was associated with decreased personal stigma, and after adjusting for age and gender, significance was retained for the I-would-not-tell-anyone subscale. Endorsing the cause “being a person of weak character” was associated with an increase in personal stigma. There is an urgent need for future research to elucidate stigma to develop effective educational initiatives for stigma reduction among Arabic-speaking leaders.